PRO development: rigorous qualitative research as the crucial foundation - Lasch, Kathryn Eilene; Marquis, Patrick; Vigneux, Marc; Abetz, Linda; Arnould, Benoit; Bayliss, Martha; Crawford, Bruce; Rosa, Kathleen (Quality of life research, 2010)
Recently published articles have described criteria to assess qualitative research in the health field in general, but very few articles have delineated qualitative methods to be used in the development of Patient-Reported Outcomes (PROs). In fact, how PROs are developed with subject input through focus groups and interviews has been given relatively short shrift in the PRO literature when compared to the plethora of quantitative articles on the psychometric properties of PROs. If documented at all, most PRO validation articles give little for the reader to evaluate the content validity of the measures and the credibility and trustworthiness of the methods used to develop them. Increasingly, however, scientists and authorities want to be assured that PRO items and scales have meaning and relevance to subjects. This article was developed by an international, interdisciplinary group of psychologists, psychometricians, regulatory experts, a physician, and a sociologist. It presents rigorous and appropriate qualitative research methods for developing PROs with content validity. The approach described combines an overarching phenomenological theoretical framework with grounded theory data collection and analysis methods to yield PRO items and scales that have content validity.